How to pee : potty training for boys - Spector, Todd (Henry Holt and Company, 2015)
Family physician Dr. Todd Spector presents a fresh and outrageously fun way to encourage little boys to give up their diapers. They can try it freestyle (in the backyard!), or give the potty a try with the help of a few props and plenty of imagination. Peeing in the potty is a lot more fun if you do it rocket style, cowboy style, or superhero style!